Stability Analysis of Systems with Interval Time-Varying Delays via a New Integral Inequality. (21st February 2020) - Ren, Zerong; Tian, Jun-kang
Abstract : This paper focuses on delay-dependent stability analysis for systems with interval time-varying delays. Based on a new integral inequality and a generalized reciprocally convex combination matrix inequality, a new delay-dependent stability criterion is obtained in terms of a linear matrix inequality (LMI). Finally, the merits of the proposed criterion are shown by two numerical examples.